2021
DOI: 10.1542/peds.2020-047803
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate Use of Remdesivir in Children With Severe COVID-19

Abstract: OBJECTIVES: Remdesivir shortens time to recovery in adults with severe coronavirus disease 2019 (COVID-19), but its efficacy and safety in children are unknown. We describe outcomes in children with severe COVID-19 treated with remdesivir. METHODS: Seventy-seven hospitalized patients <18 years old with confirmed severe acute respiratory syndrome coronavirus 2 infection received remdesivir through a compassionate-use pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 20 publications
7
78
0
8
Order By: Relevance
“… 30 Reported adverse effects of remdesivir include nausea, vomiting, and transaminase elevations and in a study of compassionate use in children, remdesivir was well tolerated, with a low incidence of serious adverse events. 39 …”
Section: Discussionmentioning
confidence: 99%
“… 30 Reported adverse effects of remdesivir include nausea, vomiting, and transaminase elevations and in a study of compassionate use in children, remdesivir was well tolerated, with a low incidence of serious adverse events. 39 …”
Section: Discussionmentioning
confidence: 99%
“…2 Remdesivir has not been evaluated in clinical trials for children, and there have been no results from systemic evaluations of pharmacokinetics, efficacy, or toxicity in younger children, although studies are ongoing (NCT04431453). 2 Recently, a report of the compassionate use of remdesivir in children with severe COVID-19 was published by Goldman et al 25 The report showed that among 77 children treated with remdesivir for severe COVID-19, most recovered and the rate of serious adverse events was low. 25 Remdesivir may cause adverse events such as transaminase elevations, hypersensitivity reactions and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, a report of the compassionate use of remdesivir in children with severe COVID-19 was published by Goldman et al 25 The report showed that among 77 children treated with remdesivir for severe COVID-19, most recovered and the rate of serious adverse events was low. 25 Remdesivir may cause adverse events such as transaminase elevations, hypersensitivity reactions and bradycardia. 12 Except the report by Goldman et al, 25 there are only a few case reports of children with COVID-19 treated with remdesivir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All children received 5 mg/kg RDV on the first day, followed by 2.5 mg/kg as considered to be safe and effective for compassionate use in children with severe COVID-19. 4 …”
Section: To the Editorsmentioning
confidence: 99%